2022
DOI: 10.3390/jcm11040927
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Rituximab in Autoimmune Disease—Associated Interstitial Lung Disease: A Prospective Cohort Study

Abstract: Objectives: To analyze the efficacy and safety of rituximab (RTX) in connective tissue disease associated with interstitial lung disease (CTD-ILD). Methods: We performed a multicenter, prospective, observational study of patients with CTD-ILD receiving rituximab between 2015 and 2020. The patients were assessed using high-resolution computed tomography and pulmonary function tests at baseline, at 12 months, and at the end of follow-up. The main outcome measure at the end of follow-up was forced vital capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
3
0
2
Order By: Relevance
“…Rituximab, tocilizumab, and abatacept have all been shown to have favorable results in recent studies, with the disease in treated individuals maintaining constant or improving as measured by PFTs. However, most of these investigations are small, uncontrolled retrospective studies, and their findings must be confirmed in RCTs [ 99 , 100 , 101 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Rituximab, tocilizumab, and abatacept have all been shown to have favorable results in recent studies, with the disease in treated individuals maintaining constant or improving as measured by PFTs. However, most of these investigations are small, uncontrolled retrospective studies, and their findings must be confirmed in RCTs [ 99 , 100 , 101 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Weitere Zulassungen für andere Autoimmunerkrankungen, wie den ANCA-assoziierten Vaskulitiden oder dem Pemphigus vulgaris, folgten. Darüber hinaus hat es auch einen hohen Stellenwert in der Therapie der Kollagenosen, insbesondere bei schweren Manifestationen und interstitieller Lungen erkrankung [17]. Allerdings profitieren nicht alle Patienten gleichermaßen, wie nicht zuletzt die hinter den Erwartungen zurückbleibenden Phase-II/III-Studien zu Rituximab und SLE demonstrierten [18,19].…”
Section: Wirkweise Der Car-t-zell-therapieunclassified
“…A total of 17 clinical studies with 1315 adult patients with RA-ILD were included, all of which were self-controlled studies. The studies were conducted in seven different countries, more precisely four in Spain, [19][20][21][22] five in Italy, [23][24][25][26][27] one in Greece, 28 four in Britain, [29][30][31][32] one in South Korea, 33 one in Japan 34 and one in the USA. 35 The age range of patients was 49-83 years, and the follow-up time was approximately 6-70 months.…”
Section: Study Characteristicsmentioning
confidence: 99%